Ateliê fotográfico: o efeito do ensino-aprendizagem de fotografia na liberação das forças criativas - Nascimento, Marden do Vale (2020)
The present research had as objective to verify if the teaching-learning of production and reading of photographs contributes to the development of desired skills in the formation of individuals able to solve unfamiliar problems through creativity. For this, an exploratory field research with a qualitative basis was carried out, using ethnographic research instruments. The aforementioned field research took place in 2019, at the Albert Sabin State College, located in Campo Grande, Rio de Janeiro. The materiality produced as a result of the research, is the prototype of a reapplicable method of teaching and learning photographic language, based on the reading and production of photographs using smartphones, which we call Ateliê Fotográfico. Such materiality was designed as a social technology. This method presented in the present work is a solution for school education, with the purpose of making it possible for high school students to develop skills related to creativity and was designed to serve individuals working in creative ecosystems and non-creative ecosystems, thus contributing to the training for the world of work and for citizenship. We used researchers from the creative economy as a theoretical reference, such as Landry, Florida and Throsby; authors who discuss the configuration of the world of work, such as Castells and Harvey; thinkers who reflect on education in the knowledge society, such as Lévy, Araya and Peters, as well as essential researchers to support the argument presented here as Oxman, who proposes an innovation cycle, Barbosa who discusses the role of art in education and Barthes and Fontcuberta who discuss issues related to the field of photography. In view of this scenario, we advocate a flexible school curriculum, with freedom of expression and that incorporates the teaching and learning of the arts, and especially photography